Copper(I) oligomers and polymers with dicyanobenzene and cyanopyridine ligands. (16th August 2016) - Broderick, Mark K.; Yang, Congqi; Pike, Robert D.; Nicholas, Aaron; May, Daniel; Patterson, Howard H.
Abstract : Graphical abstract: Complexes of [Cu(PPh3 )2 ]BF4 with dicyanobenzene (DCB) and cyanopyridine (CPy) are reported. Ortho ligands form cyclic dimers. Para ligands and m -DCB form zigzag polymers. m -CPy produces a cyclic trimer. Solvate structures reported for the o -DCB dimer. Photoluminescence ( λ exc = 341–400, λ em = 485–546 nm) is due to MLCT and metal-centered behavior. Abstract: The reaction of [Cu(MeCN)4 ]BF4 with o -, m -, or p -dicyanobenzene (DCB) or o -, m -, or p -cyanopyridine (CPy) in the presence of two equivalents of PPh3 produces DCB- or CPy-bridged copper(I) complexes. Cyclic dimers are formed for the ortho ligands, and zigzag polymers are formed using the para ligands. m -DCB produces a polymer, however m -CPy results in a cyclic trimer. Multiple lattice-bound solvates are formed upon crystallization of the o -DCB dimer from various solvents. A total of 11 X-ray crystal structures are reported for [Cu n (PPh3 ) 2n (bridge) n ](BF4 ) n ·(solvent): bridge = o -DCB, n = 2, solvent (per dimer) = none, ½ CH2 Cl2, CH2 Cl2, 2 CHCl3 /H2 O, or 2 THF; bridge = m -DCB, n = ∞, solvent = none; bridge = p -DCB, n = ∞, solvent = CH2 Cl2 (two polymorphs), bridge = o -CPy, n = 2, solvent (per dimer) = 2 toluene; bridge = m -CPy, n = 3, solvent = none; bridge = p -CPy, n = ∞, solvent = ½ acetone. All complexes are photoluminescent with excitation in the range 340–400 nm. The meta complexes emit in the blue region, while the other complexes emit in the green. Dimer complexes of o -DCB exhibit structural flexibility in the central macrocyclic ring. Complexes of m -DCB and p -CPy show orientational disorder in the ligand. Polymeric complexes show helicity. Smaller Stokes shifts are noted for DCB than for CPy complexes, suggesting less excited state distortion for cyanoaromatic ligand complexes of Cu(I).